Penerapan Metode Profile Matching Pada Promosi Jabatan Karyawan Di PT. United Tractors - Monica Honay Ng Cuar; Sulistianto Sutrisno Wanda (LPPM Universitas Bina Sarana Informatika, 2023)
The company does not yet have a system that can help provide recommendations to companies in determining the best employees as one of the conditions for promotion. The system used is GAP competence. Competency GAP compares individual competencies to job competencies so that differences in competence are obtained. This study aims to create a decision-making model for promotion using the profile matching method, in order to be able to find out the assessment process objectively and transparently in accordance with the provisions at PT. United Tractors. The method used is quantitative because the research data is in the form of numbers. The results showed that the decision support system for promotion using the profile matching method through the process of collecting and analyzing data as well as the process of determining the ranking of employees of PT. United Tractors begins with determining the Gap, the weight of the Gap value, grouping the core factors and secondary factors, calculating the total value and finally determining the ranking.